Wound inflammation post-orchiectomy affects the social dynamic of Nelore bulls - Marcelino, Caique Marques [UNESP]; Trindade, Pedro Henrique Esteves [UNESP]; García, Henry David Mogollón [UNESP]; Pupulim, Antonio Guilherme Roncada [UNESP]; Martins, Cyntia Ludovico [UNESP]; Rizzoto, Guilherme [UNESP]; Teixeira-Neto, Francisco [UNESP]; Macitelli, Fernanda; Kastelic, John Patrick; Ferreira, João Carlos Pinheiro [UNESP] (Springer Nature, 2023)
Background: Confinement of cattle imposes spatial restrictions and predisposes to aversive social encounters that can lead to contusions, wounds, pain, stress, fright, and reduced productivity. Although endogenous testosterone concentrations are linked to agonistic dominance behaviors in males, it is unknown whether decreased blood testosterone concentrations after castration alter social hierarchy rank in Nelore bulls. Therefore, in this study, we investigated the impact of the surgical would inflammation post-orchiectomy on social dynamics in a group of Nelore bulls (Bos indicus). Fourteen Nelore (Bos indicus) bulls were castrated and assessed pre- and post-surgically. Parameters evaluated were agonistic (mounting, headbutting, and fighting) and affiliative (head-play) behavior, plasma testosterone concentrations, average daily weight gain (ADG), and a score for severity of post-surgical infection. Exploratory statistics included social network analysis (SNA), hierarchy rank delta (Δ), and principal component analysis (PCA). Furthermore, statistical inferences included the Wilcoxon test, multiple logistic regression models, and Spearman's correlation. Results: The social dynamic of Nelore bulls was modified after castration based on the findings of the SNA and the PCA. The moderate correlation between the postoperative inflammation level with the Δ, and the significant effect of this level in the logistic model post-castration were partially attributed to effects of pain on social relations. Conclusions: Our findings suggest the severity of post-surgical inflammation, which has an association with pain intensity, was closely associated with changes in the social hierarchy.
Keywords: Animal welfare; Cattle; Dominance; Hierarchy; Pain